FUNCTIONAL FOOD AS A WAY TO IMPROVE NUTRITION AND DEVELOP TOURISM - Filipović, Jelena; Košutić, Milenko; Filipović, Vladimir; Ivanišević, Dragan; Vujačić, Vesna (Ekonomija - teorija i praksa, 2022)
The aim of this paper is to describe the characteristics of functional products based on cereals and their consumption in the market and tourism, in order to achieve the correlation between food, nutrition and health. All this serves the purpose of building the concept of functional food. This paper presents various technological processes utilized to obtain functional products based on cereals, such as pasta, bread and corn flakes enriched with nutrients (unsaturated fatty acids, mineral elements), probiotics and antioxidants. This paper presents the characteristics of new cereal functional products and different ways to list ingredients. Special emphasis is put on customer reception in the market as a key factor for the successful positioning of a new product.